Point-of-care ultrasound augments physical examination learning by undergraduate medical students. Issue 1143 (14th October 2020) - Wong, Chun Ka; Hai, JoJo; Chan, Kwong Yue Eric; Un, Ka Chun; Zhou, Mi; Huang, Duo; Cheng, Yang Yang; Li, Wen Hua; Yin, Li Xue; Yue, Wen Sheng; Tse, Hung Fat; Yeung, Pauline; et al.
ABSTRACT: Background: Little is known about the impact of the provision of handheld point-of-care ultrasound (POCUS) devices on physical examination skills of medical students. Methods: We describe an educational initiative that comprised a POCUS workshop followed by allocation of a POCUS device to medical students for use over the subsequent 8 weeks. They were encouraged to scan patients and correlate their physical examination findings. A mobile instant messaging group discussion platform was set to provide feedback from instructors. Physical examination skills were assessed by means of clinical examination. Results: 210 final-year medical students from the University of Hong Kong participated in the programme. 46.3% completed the end of programme electronic survey: 74.6% enjoyed using the POCUS device, 50.0% found POCUS useful to validate physical examination findings and 47.7% agreed that POCUS increased their confidence with physical examination. 93.9% agreed that the programme should be incorporated into the medical curriculum and 81.9% would prefer keeping the device for longer time from 16 weeks (45.6%) to over 49 weeks (35.3%). Medical students who participated in the POCUS programme had a higher mean score for abdominal examination compared with those from the previous academic year with no POCUS programme (3.65±0.52 vs 3.21±0.80, p=0.014), but there was no statistically significant difference in their mean score for cardiovascular examination (3.62±0.64 vs 3.36±0.93, p=0.203). Conclusion: The POCUS programme that included provision of a personal handheld POCUS device improved students' attitude, confidence and ability to perform a physical examination.